Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1017/s1041610206003188
|View full text |Cite
|
Sign up to set email alerts
|

Pre-morbid personality and depression following stroke

Abstract: Background: Depressive disorders and depressive symptoms occur commonly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 37 publications
(32 reference statements)
1
52
0
3
Order By: Relevance
“…In the same way, the finding for the capacity of emotional reactivity in this sample to predict elevated depression symptoms three months later may also indicate premorbid personality traits, such as neuroticism, that are well-established risk factors for this disorder [25]. Previous clinical studies of stroke patients have underscored the role of this trait [26,27,28], including estimates that high premorbid neuroticism conveys a 4.6-fold risk of PSD [29]. Moreover, the lack of correlation between stroke location and occurrence of PSD reported in a recent meta-analysis does not support the reverse hypothesis that negative cognitions may be caused by resulting lesions [30].…”
Section: Discussionmentioning
confidence: 83%
“…In the same way, the finding for the capacity of emotional reactivity in this sample to predict elevated depression symptoms three months later may also indicate premorbid personality traits, such as neuroticism, that are well-established risk factors for this disorder [25]. Previous clinical studies of stroke patients have underscored the role of this trait [26,27,28], including estimates that high premorbid neuroticism conveys a 4.6-fold risk of PSD [29]. Moreover, the lack of correlation between stroke location and occurrence of PSD reported in a recent meta-analysis does not support the reverse hypothesis that negative cognitions may be caused by resulting lesions [30].…”
Section: Discussionmentioning
confidence: 83%
“…These 379 studies with their full text were retrieved and reviewed for eligibility, and 300 were excluded because of ineligible study design and outcome measures. The 79 studies met all the criteria, and these were selected for initial inclusion; after review, a total of 36 articles (Kotila et al, 1998; Pohjasvaara et al, 1998; Aben et al, 2002, 2006; Carota et al, 2005; Tang et al, 2005, 2011; Leentjens et al, 2006; Storor and Byrne, 2006; Brodaty et al, 2007; Lee et al, 2007; Lindén et al, 2007; van de Port et al, 2007; Fuentes et al, 2009; Jimenez et al, 2009; Schepers et al, 2009; Snaphaan et al, 2009; Farner et al, 2010; Ayerbe et al, 2011; Altieri et al, 2012; de Man-van Ginkel et al, 2013; Yang et al, 2013, 2015; Zhang et al, 2013; De Ryck et al, 2014a,b; Li et al, 2014; Ahn et al, 2015; Lewin-Richter et al, 2015; Shi et al, 2015; van Mierlo et al, 2015; Koh et al, 2016; Kootker et al, 2016; Malhotra et al, 2016; Metoki et al, 2016; Tsai et al, 2016) were included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…2,3 A relationship between coping style and fatigue was found earlier in a study of patients with stroke. 11 In studies on patients with ischemic stroke, also a bivariate relation was found between neuroticism 12 and avoidance coping style 13 with poststroke depression. This emphasizes the need to take personality into account as a potential vulnerability factor for depression.…”
Section: Discussionmentioning
confidence: 97%